Cervical osteomyelitis: A new identity of dreaded complication following pharyngeal cancer treatment. (March 2019) - Zamparini, Emmanuel; Seng, Piseth; Bardou, Matthieu; Fakhry, Nicolas; Graillon, Thomas; Fuentes, Stéphane; Dessi, Patrick; Stein, Andreas
Highlights: Cervical osteomyelitis is a serious but rarely reported complication following the treatment of pharyngeal cancer. Cervical pain was the first sign to appear, sometimes 1 year before any other sign. Cervical pain, fever, and/or neurological signs should lead to early imaging to confirm the diagnosis. Early diagnosis and management improve the prognosis. Abstract: Background: Cervical osteomyelitis following the treatment of pharyngeal cancer with laryngectomy and chemoradiotherapy is poorly reported. Methods: Six cases of cervical osteomyelitis occurring over a 1-year period are described herein. These are reviewed alongside four cases reported previously in the literature. Results: Among the total 10 cases, the average age of the patients was 58.7 years. The period between laryngectomy and the diagnosis of cervical osteomyelitis was on average 3 years and 1 month and the male to female sex ratio was 9:1. Two patients had a history of cervical fistula with an esophageal prosthesis, one had a spontaneous cervical fistula, one had a pharyngeal cutaneous fistula, and one had an esophageal prosthesis without any fistula. At the time of diagnosis, seven had a history of cervical pain (70%) and nine had a neurological deficit (90%). Seven patients (70%) underwent surgery; one (10%) was contraindicated for a general anesthetic and two (20%) died before any intervention. The indication for surgery was a neurological deficit for six patients (60%) and the requirement for lavage and debridement for two patients (20%). The average length of antimicrobial treatment was 12.7 weeks. The outcome was favorable for six patients. Four patients died. Conclusions: Cervical osteomyelitis is a serious but rarely reported complication following the treatment of pharyngeal cancer with chemoradiotherapy and laryngectomy. Cervical pain was the first sign to appear, sometimes 1 year before any other sign. Physicians should be aware of this dreaded complication, which is probably underdiagnosed and is related to an increased mortality rate.